Andy Jarvis on genetic resources, climate change and food security - Jarvis, Andy (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
Andy Jarvis, CCAFS Theme Leader explains how the exchange of genetic resources will be an essential aspect of the adaptation of agriculture to climate change. Filmed at the 13th meeting of the Commission on Genetic Resources for Food and Agriculture (CGRFA), July 2011.